x=-1:
6(-1)>-1+5
-6<4</p>
![x = \sqrt{6} x = \sqrt{6}](https://tex.z-dn.net/?f=x%20%3D%20%20%5Csqrt%7B6%7D%20)
\sqrt{6} + 5" alt="6 \sqrt{6} > \sqrt{6} + 5" align="absmiddle" class="latex-formula">
≈15>≈7
x=14:
6*14>14+5
84>19
![x = \frac{3}{14} x = \frac{3}{14}](https://tex.z-dn.net/?f=x%20%3D%20%20%5Cfrac%7B3%7D%7B14%7D%20)
\frac{3}{14} + 5" alt="6 \times \frac{3}{14} > \frac{3}{14} + 5" align="absmiddle" class="latex-formula">
4,5<≈5,2</p>
Ответ:
![\sqrt{6} \sqrt{6}](https://tex.z-dn.net/?f=%20%5Csqrt%7B6%7D%20)
![14 14](https://tex.z-dn.net/?f=14)